Wai Ka Sonosa Naka Ngera Fuo Gamo Baiga Tungaahee Yo Ga Asopo Bino Tooni Buku (Gu Vovo Ho). Ngerafuo, Mangasunge Wa Aborosa, Abirimangapai Na Yangada Wisiga Arimoho: Tooni Buku 3 Na 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon; Porcuna Ferrer, Anna (2023)
This farmer’s handbook is a companion to (https://hdl.handle.net/10568/81286). The three booklets making up this farmer’s handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 2 is available at: [ https://hdl.handle.net/10568/151667 ] and booklet 3 is available at [ https://hdl.handle.net/10568/151666 ].